1990
DOI: 10.1093/protein/3.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic mechanism of fungal glucoamylase as defined by mutagenesis of Asp176, Glu179 and Glu180 in the enzyme from Aspergillus awamori

Abstract: Asp176, Glu179 and Glu180 of Aspergillus awamori glucoamylase appeared by differential labeling to be in the active site. To test their functions, they were replaced by mutagenesis with Asn, Gln and Gln respectively, and kinetic parameters and pH dependencies of all enzyme forms were determined. Glu179----Gln glucoamylase was not active on maltose or isomaltose, while the kcat for maltoheptaose hydrolysis decreased almost 2000-fold and the KM was essentially unchanged from wild-type glucoamylase. The The Glu18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 0 publications
7
115
0
Order By: Relevance
“…Glu179 and Glu400 have been identified as the general acid and the general base catalyst, respectively, and the pH dependencies of steady-state kinetic parameters are in accordance with a rate-determining hydrolysis involving these two catalytic residues Sierks et al, 1990;Harris et al, 1993;Frandsen et al, 1994). Also in accordance with this, the mutation of Glu400 to Gln results in a reduction of k, to 3%, showing the marked influence of this residue on the rate-determining step (Frandsen et al, 1996).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Glu179 and Glu400 have been identified as the general acid and the general base catalyst, respectively, and the pH dependencies of steady-state kinetic parameters are in accordance with a rate-determining hydrolysis involving these two catalytic residues Sierks et al, 1990;Harris et al, 1993;Frandsen et al, 1994). Also in accordance with this, the mutation of Glu400 to Gln results in a reduction of k, to 3%, showing the marked influence of this residue on the rate-determining step (Frandsen et al, 1996).…”
supporting
confidence: 56%
“…The three-dimensional structures of the native enzyme as well as of tight-binding inhibitor-enzyme complexes are known (Aleshin et al, 1992(Aleshin et al, , 1994a(Aleshin et al, , b, 1996Harris et al, 1993;Stoffer et al, 1995). Two carboxyl groups, those of Glu179 and Glu400, have been assigned, respectively, as general acid and general base catalysts in the rate-determining hydrolytic reaction step, a result based on pH dependencies of kinetic parameters (Sierks et al, 1990;Frandsen et al, 1994), chemical modification studies and structural data (Harris et a]., 1993). The general reaction scheme (Model I) of glucoamylase-catalyzed reactions based on previous stopped-flow kinetic results involves three reactions steps: (a) formation of a first enzyme-substrate association complex (ES); (b) change of conformation of the first enzyme-substrate complex to form the Michaelis complex (E:") and (c) the rate-determining, actual catalysis (Olsen et al, 1992(Olsen et al, , 1993Christensen et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The carboxylate group of the side chain of El79 has been identified as a probable acid catalyst essential for enzymic activity [22,44,451. One of its oxygen atoms is hydrogenbonded to three different side chain groups: the indole NH groups of WS2 and W120 and an amide hydrogen of Q124.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical Rescue of the Inactive E294A Mutant-Although the substantial decrease in the catalytic activity of the mutant enzyme lacking the putative nucleophilic residue is consistent with its suggested role, the identification of the catalytic residues could not be based on the reduction in activity alone. There are several examples where single mutations in proposed catalytic residues of glycoside hydrolases resulted in reduced or undetectable activity (46,47), whereas crystallographic and biochemical analyses showed that these residues are not involved directly in catalysis (48,49). To unambiguously identify Glu-294 as the nucleophilic residue of AbfA T-6, the azide rescue methodology was used.…”
Section: Figmentioning
confidence: 99%